Vagino-cutaneous fistula: unreported, under-reported or unheralded? - Ramji, Ashwath Narayan (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2019)
Fistulas are communicating tracts between two surfaces, linking structures and planes that should, under normal circumstances, not be in dialogue. They may be congenital or acquired and are most commonly associated with the gastrointestinal and ano-rectal territories, where they link two different organ systems internally, or track outwards, creating a communicating channel between the internal viscera and the skin surface. Vaginal fistulas on occasion result from perineal tears due to traumatic delivery, or less commonly, infection or non-healing of the episiotomy wound, and are of the rectovaginal or vesicovaginal variety. Very rarely, the channel from the vagina tracks to an opening in the skin. This is the report of a patient who developed the rare vagino-cutaneous fistula following a normal vaginal delivery with episiotomy, and review of the limited literature available about the peculiar entity, so rare that no previous reports of vagino-cutaneous fistulas developing after vaginal delivery with episiotomy could be found.